Mater Nostra: The Anti-blasphemy Message of the Feminist Punk Prayer - Volkova, Elena (Religion & gender, 2014)
In this essay I develop a blasphemy counter-discourse arguing that it was ecclesial and state authorities who committed blasphemies, which were condemned by Pussy Riot’s Punk Prayer. Thus, the performance in this respect may be interpreted as an anti-blasphemy protest. The blasphemy list includes the collaboration of the church with the authoritarian state, known as heresy of Sergianism; Caesar and Temple idolatry, blasphemy against the Holy Spirit, Virgin Mary and Folly for Christ’s sake. The Punk Prayer may be interpreted as a feminine version of the Lord’s Prayer - Mater Nostra. Several corporeal narratives in the background - women’s dress code and rape debates, Virgin Mary’s belt, and its alleged miraculous ability to help women to deliver a baby - may be seen as allegories of feminist versus patriarchal opposition in Russian religious and political culture.